Code status and resuscitation options in the electronic health record. (February 2015) - Bhatia, Haresh L.; Patel, Neal R.; Choma, Neesha N.; Grande, Jonathan; Giuse, Dario A.; Lehmann, Christoph U.
Abstract: Aim: The advance discussion and documentation of code-status is important in preventing undesired cardiopulmonary resuscitation and related end of life interventions. Code-status documentation remains infrequent and paper-based, which limits its usefulness. This study evaluates a tool to document code-status in the electronic health records at a large teaching hospital, and analyzes the corresponding data. Methods: Encounter data for patients admitted to the Medical Center were collected over a period of 12 months (01-APR-2012–31-MAR-2013) and the code-status attribute was tracked for individual patients. The code-status data were analyzed separately for adult and pediatric patient populations. We considered 131, 399 encounters for 83, 248 adult patients and 80, 778 encounters for 55, 656 pediatric patients in this study. Results: 71% of the adult patients and 30% of the pediatric patients studied had a documented code-status. Age and severity of illness influenced the decision to document code-status. Demographics such as gender, race, ethnicity, and proximity of primary residence were also associated with the documentation of code-status. Conclusion: Absence of a recorded code-status may result in unnecessary interventions. Code-status in paper charts may be difficult to access in cardiopulmonary arrest situations and may result in unnecessary and unwanted interventions and procedures. Documentation of code-status in electronic records creates a readily available reference for care providers.